2003
DOI: 10.1111/1468-5884.t01-1-00045
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage in the perceived duration of speech and tone by acoustic replacement1

Abstract: To investigate mechanisms for perceiving the duration of an auditory event, an effect of perceptual grouping upon perceived duration was studied psychophysically. In the first experiment, the perceived duration of a spoken word was measured under three conditions of acoustic continuity (i.e., (a) intact, (b) noise-replaced, and (c) gap-replaced) as a function of the duration of the target stimulus. Under the noise-replaced condition, a portion of the target stimulus was physically replaced with a noise burst. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 19 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…Although several experiments have provided enough counter evidence to refute this hypothesis as a general framework to account for the shrinkage of duration by noise, we cannot deny that contextual information contributes to the perceptual judgment of temporal structure. The results of Tsuzaki and his colleagues also showed that the shifts of PSE depended on a standard duration, and this effect of the standard duration can be regarded as an example of contextual effects [1,3].…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Although several experiments have provided enough counter evidence to refute this hypothesis as a general framework to account for the shrinkage of duration by noise, we cannot deny that contextual information contributes to the perceptual judgment of temporal structure. The results of Tsuzaki and his colleagues also showed that the shifts of PSE depended on a standard duration, and this effect of the standard duration can be regarded as an example of contextual effects [1,3].…”
Section: Introductionmentioning
confidence: 89%
“…Tsuzaki and his colleagues have demonstrated that the duration of a sound is perceived to be slightly shorter when a portion is replaced by a noise burst than when it is kept intact [1][2][3]. They tested several hypothesis to explain this phenomenon and concluded that the evidence-gating hypothesis is the most acceptable [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations